PS22 Life Course Socio-Economic Position and Quality of Life in Adulthood: A Systematic Review of Life Course Models. (17th September 2012) - Niedzwiedz, C; Katikireddi, SV; Pell, J; Mitchell, R
Abstract : Background: Measurement and determinants of quality of life are of increasing interest to researchers and policymakers. A relationship between current socio-economic position and subjective quality of life has been demonstrated, using wellbeing, life and needs satisfaction approaches. Less is known regarding the influence of different socio-economic trajectories across the life course and their subsequent effect on quality of life. Several conceptual models have been proposed to help explain potential life course effects on health, including accumulation, latent, pathway and social mobility models. This systematic review aimed to apply these models to studies investigating life course socio-economic effects on quality of life, in order to assess which model(s) best described any relationship. Methods: A review protocol was developed detailing explicit inclusion and exclusion criteria, search terms, data extraction items and quality appraisal procedures. Literature searches were performed in 12 electronic databases during January 2012 and the references and citations of included articles were checked for additional relevant articles. Narrative synthesis was used to analyse the results and studies were categorised into groups based on the life course design implemented. Results: After screening 7, 566 records, 12 studies met the eligibility criteria. The included articles used data from 10 different datasets and five countries. Study quality varied and heterogeneity was high. Five studies assessed the latent model, two assessed the pathway model and three tested the accumulation model. Seven studies assessed social mobility models (inter-generational mobility in three, intra-generational mobility in five and one included both types). More evidence was found to support the latent model among women (but results were contradictory) and mixed evidence was found for intra-generational mobility and pathway effects. Associations also tended to vary by gender. Few studies were identified for accumulation and inter-generational mobility effects and heterogeneity of these studies resulted in limited synthesis. Conclusion: A lack of available and comparable evidence prevented the identification of the optimal life course model(s). Different target populations, outcomes and methodologies used between studies likely contributed to the mix of results. To improve the potential for synthesis in this area, future studies should aim to increase study comparability. Recommendations include testing all life course models within studies and the use of multiple measures of socio-economic position and quality of life. To enable investigation of between-country differences, the increased collection, harmonisation and utilisation of comparable cross-national data would be beneficial.